2021
DOI: 10.26434/chemrxiv.14205929
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A Recommendation System to Predict Missing Adsorption Properties of Nanoporous Materials

Abstract: Nanoporous materials (NPMs) selectively adsorb and concentrate gases into their pores, and thus could be used to store, capture, and sense many different gases. Modularly synthesized classes of NPMs, such as covalent organic frameworks (COFs), offer a large number of candidate structures for each adsorption task. A complete NPM-property table, containing measurements of the relevant adsorption properties in the candidate NPMs, would enable the matching of NPMs with adsorption tasks. However, in practice the NP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…The authors conducted a series of experiments using real-world datasets and the results demonstrated that the proposed method outperforms the baseline method in terms of rating prediction and ranking performance [11]. Sturluson A designed a recommendation system based on covalent organic frameworks (COF), and experimentally demonstrated that this COF recommendation system was able to reasonably rank COF according to most of the adsorption performance metrics, but the predictive effectiveness of the system decreased dramatically when the percentage of missing entries exceeded 60% [12].…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors conducted a series of experiments using real-world datasets and the results demonstrated that the proposed method outperforms the baseline method in terms of rating prediction and ranking performance [11]. Sturluson A designed a recommendation system based on covalent organic frameworks (COF), and experimentally demonstrated that this COF recommendation system was able to reasonably rank COF according to most of the adsorption performance metrics, but the predictive effectiveness of the system decreased dramatically when the percentage of missing entries exceeded 60% [12].…”
Section: Related Workmentioning
confidence: 99%
“…The original input is a high-dimensional sparse one-hot code, which is converted into a low-dimensional dense vector by the embedding layer for network training. The output ( ) 0 a of the embedding layer can be described as in equation (3) [19]. a into the DNN network, the forward propagation process of the DNN network can be described in equation ( 4):…”
Section: ( )mentioning
confidence: 99%